Wide QRS complex and the risk of major arrhythmic events in Brugada syndrome patients: A systematic review and meta‐analysis. Issue 1 (27th December 2019) - Rattanawong, Pattara; Kewcharoen, Jakrin; Techorueangwiwat, Chol; Kanitsoraphan, Chanavuth; Mekritthikrai, Raktham; Prasitlumkum, Narut; Puttapiban, Prapaipan; Mekraksakit, Poemlarp; Vutthikraivit, Wasawat; Sorajja, Dan
Abstract: Background: Brugada syndrome (BrS) is an inherited arrhythmic disease associated with an increased risk of major arrhythmic events (MAE). Previous studies reported that a wide QRS complex may be useful as a predictor of MAE in BrS patients. We aimed to assess the correlation of wide QRS complex with MAE by a systematic review and meta‐analysis. Methods: We comprehensively searched the databases of MEDLINE and EMBASE from inception to June 2019. Included studies were cohort and case control studies that reported QRS duration and the relationship between wide QRS complex (>120 milliseconds) and MAE (sudden cardiac death, sudden cardiac arrest, ventricular fibrillation, sustained ventricular tachycardia, or appropriate shock). Data from each study were combined using the random‐effects model. Results: Twenty‐two studies from 2007 to 2018 were included in this meta‐analysis involving 4, 814 BrS patients. The mean age was 46.1 ± 12.8 years. The patients were predominately men (77.6%). Wide QRS duration was an independent predictor of MAE (pooled risk ratio 1.55, 95% confidence interval: 1.04‐2.30, P  = .30, I 2  = 38.4%). QRS duration was wider in BrS who had history of MAE (weight mean difference = 8.12 milliseconds, 95% confidence interval: 5.75‐10.51 milliseconds). Conclusions: Our study demonstrated that QRS duration is wider in BrS who had history of MAE, and a wide QRS complex is associated with 1.55 times higher risk of MAE in BrS populations. Wide QRS complex can be considered for risk stratification in prediction of MAE in patients with BrS, especially when considering implantable cardioverter‐defibrillator placement in asymptomatic patients. Abstract : Our study demonstrated that a wide QRS complex is associated with 1.55 times higher risk of major arrhythmic events in Brugada syndrome populations. Wide QRS complex can be considered for risk stratification in prediction of MAE in patients with BrS, especially when considering implantable cardioverter‐defibrillator placement in asymptomatic patients.